Pengaruh Media Sosial, Electronic Word of Mouth, dan Variasi Produk terhadap Keputusan Pembelian (Studi Kasus Produk Makanan Oke Enak Rawamangun) - Suhardi, Yusuf; Akhmadi, Ali; Darmawan, Arya; Naili, Naili (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research is intended to examine the effect of Social Media, Electronic Word Of Mouth, and Product Variations on Purchase Decisions, namely a food product produced by Okay Enak Rawamangun.The type of research used is associative research with a quantitative approach, using the latest SPSS 26.0 software. In this study, users who had purchased food items with the Oke Enak Rawamangun product. Sampling was based on the purposive sampling method, with a total sample of 97 buyers of Oke Enak. In terms of data used in research is primary data. In collecting data using a questionnaire. Hypothesis testing using the t test, f test, and the coefficient of determination test (R2) to see how much it contributes to purchasing decisions.This research produces evidence that (1) Social Media has a significant effect on Purchase Decisions in the field of Ok Delicious Rawamangun food, then (2) Electronic Word Of Mouth has a significant effect on Purchase Decisions, (3) Product Variation has a significant effect on Purchase Decisions and it is also proven (4). Social Media, Electronic Word Of Mouth, and Product Variations collectively have an influence on the decision to purchase Okay Enak Rawamangun food products.